Louise Trapeze can SO save the day - Ostow, Micol (Louise Trapeze, 2016)
The Sweet Potato Circus is in trouble, and Louise and her best friend, Stella, will do anything to save their circus--even if it means joining forces with their sworn enemy, Ferret-breath Fernando.